Deforestation mechanism: a survey - Wibowo, D.H.; Byron, R.N. (Environment Programme, University of Queensland, 1997)
Numerous published economic models of tropical deforestation are reviewed, in four categories: - a Neo-Malthusian approach, often nebulous and imprecise in terms of causal processes, which sees population pressure as the underlying cause of tropical deforestation; - those focusing on government failures - particularly on misdirected government policies in other sectors that result in excessive and inappropriate deforestation; sectoral (e.g. log export ban) policies; and the general failure of supervisory institutions of governance, including corruption. This approach puts great emphasis on the effects of government interventions; - a microeconomic approach which considers the economic rationality of forest clearance from a farmer's perspective, and explains how various forms of market failure, e.g. poorly defined property rights, poorly-designed logging contracts and undervaluation of forest benefits at the local, regional or global level, all contribute to deforestation; and - a macroeconomic emphasis which explores the alleged links between debt and deforestation, leading to debt-for-nature swaps being proposed as a means for reducing deforestation rate in developing countries. The authors conclude that both the government failures and micro-economic analyses are particularly relevant to understanding current deforestation processes and policy options in Indonesia.